Porous ceramic laminate and separation membrane
By designing the ceramic layer structure of the first and second layers in the ceramic membrane, using specific metal oxide composition and pore structure, the problem of ceramic membrane interface peeling is solved, and the peel strength and performance stability of the film are improved.
Patent Information
- Application Number
- JP2023144371
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, multi-layered ceramic films are prone to interface peeling problems during application, which affects their performance and stability.
A ceramic membrane structure is adopted, in which the first layer and the second ceramic layer are directly superimposed, the first layer contains metal oxide X, the second layer contains metal oxide Y of Ti and Al, the molar ratio of Ti/Al is between 0.005 and 0.10, and the pore capacity and contact area are ensured by the optimization of appropriate pore structure and element proportions.
The peel strength between the first and second layers is effectively improved, and the overall performance and stability of the film is enhanced, especially maintaining high permeability when the fluid flows through.
Smart Images

Figure 2025037436000001 
Figure 2025037436000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a porous ceramic laminate and a separation membrane. [Background technology]
[0002] Porous ceramic bodies are used in various fields as membranes having functions such as separation, concentration, or filtration of fluids, such as gases or liquids, such as microfiltration membranes, ultrafiltration membranes, nanofiltration membranes, reverse osmosis membranes, ion exchange membranes, and gas separation membranes.
[0003] For example, Patent Document 1 discloses a monolithic separation membrane structure comprising a substrate made of a porous material and having a plurality of through holes, a first support layer formed on the inner surfaces of the plurality of through holes, and a separation membrane disposed inside the first support layer, the first support layer containing alumina, titania, and at least one of silica and magnesia. Patent Document 1 describes that the strength of the first support layer can be improved by containing the above-mentioned components in the first support layer.
[0004] Furthermore, Patent Document 2 discloses a ceramic porous body obtained by binding ceramic particles with a binder of glass that contains a metal oxide selected from Li2O, Na2O, and the like, with the remainder being SiO2 and unavoidable impurities, and describes that such a ceramic porous body can be used for a long period of time as a filtration filter, etc., even in environments exposed to acids and alkalis. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2015 / 146571 [Patent Document 2] JP 2003-238257 A Summary of the Invention [Problem to be solved by the invention]
[0006] It is important that porous ceramic bodies suitable for use in the above-mentioned fields allow fluids to flow easily through the porous ceramic body while fully performing functions such as separation, i.e., that the pressure loss of the fluid is small, and therefore the porous ceramic body is usually composed of a laminate of two or more layers including a functional layer with a small pore diameter and a support layer with a large pore diameter that supports the functional layer. In a laminate in which two or more layers are laminated, peeling will occur at the interface when a load is applied to the laminate unless the bond at the interface is strong.
[0007] The aforementioned Patent Documents 1 and 2 also disclose a laminate as a structure of a separation membrane, but do not consider peeling at the lamination interface. Therefore, an object of the present invention is to provide a porous ceramic laminate in which two or more types of layers are laminated, in which peeling at the lamination interface is suppressed. [Means for solving the problem]
[0008] The present invention which achieves the above object is as follows. [1] A porous ceramic laminate having a first porous layer and a second porous layer directly laminated on the first porous layer, the first porous layer comprises a metal oxide X; the second porous layer contains a metal oxide Y, the metal oxide Y containing Ti and Al; the molar ratio of Ti / Al in the second porous layer is 0.005 or more and less than 0.10; A porous ceramic laminate having a cumulative pore volume V1 of pores with diameters of 0.98 to 200 μm of 0.115 mL / g or more and less than 0.259 mL / g. [2] The porous ceramic laminate according to [1], wherein the first porous layer contains Na and Ca elements, and the mass ratio of Na / Ca in the first porous layer is greater than 1.16 and less than 100. [3] The porous ceramic laminate according to [1] or [2], wherein the first porous layer contains Na and Al elements, and the mass ratio of Na / Al in the first porous layer is greater than 0.0049 and less than 0.10. [4] The porous ceramic laminate according to any one of [1] to [3], wherein the cumulative pore volume V1 of pores having a pore diameter of 0.98 to 200 μm:V1 / Vt is greater than 0.88 and less than 0.99, relative to the cumulative pore volume Vt of pores having a pore diameter of 0.112 to 200 μm. [5] The porous ceramic laminate according to any one of [1] to [4], wherein the metal oxide X contains Al2O3. [6] The porous ceramic laminate according to any one of [1] to [5], which is in a tubular or monolithic shape. [7] A separation membrane comprising the porous ceramic laminate according to any one of [1] to [6]. Effect of the Invention
[0009] According to the present invention, it is possible to provide a porous ceramic laminate having improved peel strength between the first porous layer and the second porous layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The porous ceramic laminate of the present invention is a porous ceramic laminate having a first porous layer and a second porous layer directly laminated on the first porous layer, wherein the first porous layer contains a metal oxide X, the second porous layer contains a metal oxide Y, and the metal oxide Y contains Ti and Al, the molar ratio of Ti / Al in the second porous layer is 0.005 or more and less than 0.10, and the cumulative pore volume V1 of pores with diameters of 0.98 to 200 μm is 0.115 mL / g or more and less than 0.259 mL / g.
[0011] (1) Pore distribution of porous ceramic laminates (1-1) Cumulative pore volume V1 of pore diameters of 0.98 to 200 μm The pores having a diameter in the range of 0.98 to 200 μm are preferably present in the first porous layer. LD-max (Details will be described later) is the pore diameter D of the second porous layer LD-maxIt is preferable that the cumulative pore volume V1 is larger than the first porous layer, and the cumulative pore volume V1 having a pore diameter in the range of 0.98 to 200 μm is important in improving the peel strength at the interface between the first porous layer and the second porous layer. If the cumulative pore volume V1 is small, the surface of the second porous layer of the first porous layer becomes flat, so that the contact area between the two is reduced and the peel strength is reduced. On the other hand, even if the cumulative pore volume V1 is large, the second porous layer cannot enter the pores on the surface of the first porous layer, and only the edges of the pore openings are in contact, so that the areas where the first porous layer and the second porous layer cannot contact each other increase, and the contact area is reduced and the peel strength is reduced. Therefore, in the present invention, V1 is 0.115 mL / g or more and less than 0.259 mL / g.
[0012] V1 is preferably 0.13mL / g or more, more preferably 0.14mL / g or more, and preferably 0.24mL / g or less, more preferably 0.22mL / g or less. V1 is also preferably 0.14mL / g or more and 0.24mL / g or less, or 0.14mL / g or more and 0.22mL / g or less. V1 is also preferably 0.20mL / g or more and 0.24mL / g or less, and by doing so, the decrease in permeability when switching from a high flow rate to a low flow rate can be suppressed.
[0013] (1-2) Cumulative pore volume V1 of pores with a pore diameter of 0.98 to 200 μm: V1 / Vt The cumulative pore volume Vt is a pore volume including pores in the second porous layer, that is, pores with small pore diameters, with a lower limit of 0.112 μm. In contrast, the cumulative pore volume V1 is a value that mainly reflects the pore distribution of the first porous layer, as described above. In other words, V1 / Vt is a value that reflects the influence of small pores in the second porous layer. V1 / Vt is preferably greater than 0.88 and less than 0.99, and by doing so, it is possible to suppress the decrease in permeability when the flow rate of the fluid is switched from a high flow rate to a low flow rate. V1 / Vt is more preferably 0.92 or more and less than 0.99, and even more preferably 0.94 or more and less than 0.99.
[0014] Both of the above V1 and Vt can be measured by mercury intrusion porosimetry.
[0015] (2) Structure and shape of porous ceramic laminate The porous ceramic laminate of the present invention includes a first porous layer and a second porous layer, and the second porous layer is directly laminated on the first porous layer. Directly laminated means that the first porous layer and the second porous layer are laminated without any other layer. As long as a part of the second porous layer is in contact with the first porous layer, the remaining part may be laminated on the first porous layer via air present due to pores present on the surface of the first porous layer or inorganic particles other than the metal oxide particles constituting the second porous layer. The part where the second porous layer and the first porous layer are in contact may be the pores of the pores present on the surface of the first porous layer.
[0016] The shape of the porous ceramic laminate is not particularly limited, and may be, for example, a plate, a tube, a honeycomb, or a monolith. A tube, a honeycomb, or a monolith is preferable, and a monolith is preferable, particularly when used as a substrate of a ceramic filter for gas separation. The monolith means a columnar (cylindrical, rectangular, elliptical, etc.) shape having a plurality of holes (preferably a cylindrical shape) penetrating in the axial direction, and the honeycomb means a shape in which hollow three-dimensional figures (regular hexagonal, rectangular, triangular, etc.) penetrating in the axial direction are stacked without gaps. When the porous ceramic laminate is tubular, the second porous layer is preferably formed only on the inner peripheral surface, only on the outer peripheral surface, or both the inner peripheral surface and the outer peripheral surface of the tube, more preferably formed only on the inner peripheral surface or only on the outer peripheral surface, and even more preferably formed only on the inner peripheral surface. When the porous ceramic laminate is monolithic, the second porous layer is preferably formed only on the inner surface of each through hole of the monolith shape.
[0017] The thickness (average value) of the porous ceramic laminate is, for example, 450 to 10,000 μm, and more preferably 500 to 6,000 μm. When the porous ceramic laminate has a monolithic or honeycomb shape, the thickness may be the average value of the closest distance between adjacent through holes in a plane perpendicular to the axis. The length of the porous ceramic laminate in the longitudinal direction is, for example, 50 to 5000 mm. The length in the longitudinal direction means, for example, the length of the long side in the case of a plate shape, and the length in the axial direction in the case of a tube shape, honeycomb shape, or monolith shape. When the porous ceramic laminate is tubular, the outer diameter is, for example, 5 mm to 20 mm, and the inner diameter of the tube is, for example, 1 mm to 15 mm. When the porous ceramic laminate is honeycomb or monolithic, that is, when it has a plurality of through holes, the outer diameter is, for example, 5 mm to 100 mm, and the inner diameter of each through hole (particularly a cylindrical shape) is, for example, 0.1 mm to 10 mm.
[0018] (3) First porous layer The first porous layer preferably contains a metal oxide X, and the metal oxide X may be one type or two or more types. The metal oxide X preferably contains at least one oxide selected from the group consisting of Al, Ca, Na, Fe, and Si, and more preferably contains Al2O3. The at least one oxide selected from the group consisting of Al, Ca, Na, Fe, and Si includes oxides containing only one type of metal element, as well as composite oxides containing two or more types of metal elements.
[0019] The first porous layer preferably contains Na and Ca elements, and the Na and Ca elements may be contained as Na oxide or Ca oxide. The first porous layer preferably contains Na and Ca elements, and the mass ratio of Na / Ca in the first porous layer is more than 1.16 and less than 100. Na and Ca are elements that can act as assistants for promoting the bonding of metal oxides, and when the mass ratio of Na / Ca is in the above range, the peel strength between the first porous layer and the second porous layer can be improved, and the larger this value is, the more the decrease in permeability can be suppressed when the speed of the fluid permeating the laminate of the present invention is switched from a high flow rate to a low flow rate. The mass ratio of Na / Ca is more preferably 2 or more and 80 or less, and even more preferably 5 or more and 70 or less.
[0020] It is also preferred that the first porous layer contains Na and Al elements, and the mass ratio of Na / Al in the first porous layer is more than 0.0049 and less than 0.10. The Na and Al elements may be contained as Na oxide or Al oxide (preferably Al2O3). When the mass ratio of Na / Al is within the above range, the decrease in permeability when switching from a high flow rate to a low flow rate can be suppressed. The mass ratio of Na / Al is more preferably 0.01 or more and 0.07 or less, and even more preferably 0.01 or more and 0.05 or less.
[0021] The amount of elements contained in the first porous layer can be measured by X-ray fluorescence analysis, and can be measured by quantifying the first porous layer using the FP method using a commercially available X-ray fluorescence analyzer such as ZSX PrimusII (manufactured by Rigaku Corporation).
[0022] As described above, the pores having a diameter of 0.98 to 200 μm are preferably present in the first porous layer, and the cumulative pore volume of the pores having a diameter of 0.98 to 200 μm in the first porous layer preferably satisfies the condition of the cumulative pore volume V1 in the porous ceramic laminate of the present invention, including the preferred range. LD-maxThe log differential pore volume is a value expressed as dV / d(logD) where V is the pore volume, D is the pore diameter, dV is the difference in pore volume between measurement points, and d(logD) is the difference in logarithm of the pore diameter. LD-max can be calculated by measuring the porous ceramic laminate by mercury intrusion porosimetry to obtain the log differential pore volume distribution.
[0023] The substrate capable of forming the first porous layer having such a cumulative pore volume is preferably a substrate having a pore diameter of 0.98 to 200 μm and a cumulative pore volume of 0.13 to 0.25 mL / g, and commercially available substrates such as an alumina porous pipe manufactured by Iwao Porcelain Industry Co., Ltd., and a PM filter tube, AF filter tube, and AF-D filter tube manufactured by Nikkato Co., Ltd. can be used. In addition, a substrate having a pore diameter of 0.98 to 200 μm and a cumulative pore volume of 0.13 to 0.25 mL / g can be prepared by the following method.
[0024] The substrate for the first porous layer can be produced by kneading a raw material mixture containing inorganic particles having an average particle size of 0.05 to 10 μm as a raw material for metal oxide X and a pore-forming agent having a diameter of 2 μm to 50 μm, forming the raw material into a predetermined shape, and drying and firing the obtained molded body to burn off the pore-forming agent.
[0025] The inorganic particles used as a raw material preferably contain one or more particles selected from the group consisting of aluminum oxide, calcium hydroxide, sodium hydroxide, iron oxide, and silicon oxide, and more preferably contain aluminum oxide.
[0026] The average particle size of the inorganic particles is from 0.05 to 10 μm, preferably from 0.05 to 3 μm, and more preferably from 0.1 to 1 μm.
[0027] The inorganic particles are aggregates for the base material for the first porous layer, and by using inorganic particles having the above-mentioned particle size, the aggregate portion becomes a dense ceramic with few pores, making it possible to control the pore structure with a pore-forming agent described below, and the cumulative pore volume for pores with diameters of 0.98 to 200 μm can be set to 0.13 to 0.25 mL / g. If the particle size of the inorganic particles is larger than the above range, irregular coarse pores are generated between the particles, making it difficult to control the pore structure.
[0028] In the inorganic particles, the mass ratio of Na / Ca is preferably adjusted to be more than 1.16 and less than 100. The mass ratio of Na / Ca in the inorganic particles may be adjusted to be in the same range as the mass ratio of Na / Ca in the first porous layer, which is a preferred embodiment. In addition, the mass ratio of Na / Al in the inorganic particles is preferably adjusted to be more than 0.0049 and less than 0.10, and the mass ratio of Na / Al may be adjusted to be in the same range as the mass ratio of Na / Al in the first porous layer, which is a preferred embodiment. In order to control the ratio of each element within the above range, the mixing ratio of each inorganic particle may be adjusted so as to satisfy the above mass ratio when mixing the inorganic particles. The mixing ratio of each inorganic particle can be adjusted by weighing the raw materials of the inorganic particles containing Na and Ca, such as sodium hydroxide and calcium hydroxide, and then separating and mixing the raw materials so that the mass ratio of Na / Ca is more than 1.16 and less than 100.
[0029] The pore-creating agent is preferably a polymer particle controlled to be spherical, which is mixed with the inorganic particles, molded, and then fired to burn off the pore-creating agent, forming pores in the shape of the pore-creating agent, and a base material for the first porous layer having a pore diameter of 0.98 to 200 μm and a cumulative pore volume of 0.13 to 0.25 mL / g can be obtained. The particle size of the polymer particles used as the pore-creating agent is 2 μm or more and 50 μm or less, preferably 3 μm or more and 50 μm or less, and more preferably 8 μm or more and 30 μm or less. By setting the particle size within this range, pores with a pore diameter in the range of 0.98 to 200 μm can be created after firing, and when a pore-creating agent with a particle size smaller than 3 μm is used, the pore diameter becomes smaller than 0.98 μm, and when the particle size is larger than 50 μm, the strength of the base material becomes insufficient.
[0030] The polymer constituting the polymer particles can be any polymer such as an acrylic resin or a styrene resin, and commercially available polymer particles can be used.
[0031] The mixing ratio of the inorganic particles and the pore-creating agent is preferably adjusted so that the volume of the pore-creating agent is 0.13 to 0.25 mL per 1 g of inorganic particles, taking into consideration the density of the raw materials of the inorganic particles and the densities of the raw materials of the pore-creating agent, and the fact that the pore-creating agent is burned off after firing.
[0032] In addition to the inorganic particles and pore-forming agent described above, the components to be blended into the raw material mixture may include, for example, an organic binder, a dispersant, a surfactant, and water.
[0033] Examples of the organic binder include methyl cellulose, hydroxypropoxyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, and polyvinyl alcohol.
[0034] Examples of dispersants and surfactants include fatty acid salts, alkyl sulfate salts, polyoxyethylene alkyl ether sulfate salts, alkylbenzene sulfonates, alkylnaphthalene sulfonates, alkyl sulfosuccinates, alkyl diphenyl ether disulfonates, alkyl phosphates, polycarboxylates, polyacrylates, aliphatic quaternary ammonium salts, aliphatic amine salts, polyoxyethylene alkyl ethers, polyoxyethylene alcohol ethers, polyoxyethylene glycerin fatty acid esters, polyoxyethylene sorbitan (or sorbitol) fatty acid esters, polyethylene glycol fatty acid esters, alkyl betaines, amine oxides, and cationic cellulose derivatives.
[0035] After kneading the raw material mixture, it is molded into a desired shape to obtain a molded body. A preferred example of the kneading method is a method in which inorganic particles, a pore-forming agent, and water are first mixed to obtain a slurry, and then a binder, a surfactant, and an appropriate amount of water are added to the slurry and kneaded.
[0036] The shape of the molded body (i.e., the shape of the first porous layer) is not particularly limited, and can be various shapes such as a plate shape, a tube shape, a honeycomb shape, or a monolith shape depending on the application. For example, when used as a substrate for a ceramic filter for gas separation, a monolith shape is preferable. In order to mold the raw material into a monolith shape, it is preferable to adopt a molding method such as extrusion molding.
[0037] The obtained molded body is dried by an appropriate drying method and then fired. The drying method is not particularly limited, but a drying method using microwaves, hot air, or the like is preferable. In addition, after drying the molded body, and before firing, a calcination may be appropriately performed to burn and remove the pore-forming agent in the molded body. In general, the calcination temperature may be about 600°C. There is no particular limit to the calcination time, but it is usually about 1 to 10 hours. The calcination atmosphere may be appropriately selected from air, nitrogen, and the like.
[0038] The firing temperature is preferably 1400 to 1600°C, and more preferably 1400 to 1550°C. If the firing temperature is less than 1400°C, sintering may not proceed sufficiently. On the other hand, if the firing temperature exceeds 1600°C, the pores shrink, making it difficult to adjust the pore structure. The firing time is not particularly limited, but is usually about 1 to 10 hours. The firing atmosphere can be appropriately selected from air, nitrogen, and the like.
[0039] The thickness of the first porous layer is preferably 400 to 8000 μm. When the first porous layer is monolithic, the thickness may be the average value of the closest distance between adjacent through holes on a plane perpendicular to the axis.
[0040] (4) Second porous layer The second porous layer contains a metal oxide Y, which contains Ti and Al. The metal oxide Y may be one type or two or more types, and it is preferable that the metal oxide Y contains Ti and Al by being present in any of the forms of TiO2, Al2O3, and a composite oxide containing Ti and Al. Ti oxide is useful for improving the strength of metal oxides, and the presence of Ti oxide in the second porous layer can strengthen the bond between the first porous layer and the second porous layer, thereby improving the peel strength between them. The molar ratio of Ti / Al in the second porous layer is 0.005 or more and less than 0.10. The molar ratio of Ti / Al is preferably 0.01 or more, more preferably 0.03 or more, and may be 0.09 or less, or may be 0.08 or less.
[0041] As long as the metal oxide Y contains Ti and Al, it may contain one or more oxides containing metals other than Ti and Al. Examples of oxides containing metals other than Ti and Al include one or more oxides containing at least one of Fe, Si, Zr, Mg, Cr and Y. The oxides containing at least one of Fe, Si, Zr, Mg, Cr and Y include oxides containing only one type as a metal element, as well as composite oxides containing two or more types of metal elements. Commercially available oxide particles can be used for the oxide containing Ti, and examples of the oxides include STS-21, ST-01, ST-21, ST-31, ST-41, STS-01, STS-02 manufactured by Ishihara Sangyo Kaisha, Ltd., MT-500B, MT-600B, MT-700B manufactured by Teika Corporation, and TAF-520, TAF-500, TAF-1500 manufactured by Fuji Titanium Industries Co., Ltd., and STS-21, STS-01, and STS-02 manufactured by Ishihara Sangyo Kaisha, Ltd. are preferred.
[0042] The presence and content ratio of elements contained in the second porous layer can be measured by SEM-EDX analysis, and can be measured by performing a composition analysis of the second porous layer using a commercially available SEM-EDX device such as JSM-7500F (manufactured by JEOL Ltd.).
[0043] Pore diameter D of the second porous layer LD-max is, for example, 0.1 to 2.0 μm, preferably 0.1 to 1 μm, more preferably 0.1 to 0.5 μm, and further preferably 0.2 to 0.4 μm. LD-max As described in the description of the first porous layer, this refers to the pore diameter at which the log differential pore volume value is maximized, and can be obtained by measuring the porous ceramic laminate using mercury intrusion porosimetry.
[0044] The thickness of the second porous layer is, for example, 1 μm to 3 mm, preferably 2 μm to 2 mm, more preferably 3 to 300 μm, even more preferably 20 to 100 μm, particularly preferably 25 to 80 μm, and most preferably 30 to 60 μm. The thickness of the second porous layer can be determined by the following procedure. First, an image of a cross section parallel to the lamination direction of the first porous layer and the second porous layer is obtained. In the image, the total length of the surface of the second porous layer facing the first porous layer is determined to be equal to or smaller than the pore diameter D at which the value of the log differential pore volume of the first porous layer is maximized. LD-max An image is obtained so that the area is 10 times larger than the area of the first porous layer, and only the second porous layer is extracted by image analysis. Then, the thickness (length in the stacking direction) of the second porous layer in the obtained image is measured at five or more points, and the average thickness of the measured points is calculated. Note that the cross section parallel to the stacking direction of the first porous layer and the second porous layer can be, for example, a cross section perpendicular to the longitudinal direction of the stack (for example, the axial direction when the stack is tubular or monolithic).
[0045] (5) Properties of porous ceramic laminates (5-1) Peel strength The peel strength between the first and second porous layers in the porous ceramic laminate of the present invention can be evaluated by measuring the pencil hardness from the second porous layer side of the porous ceramic laminate under the conditions described in the Examples. The second porous layer is a layer containing a metal oxide and usually has a high hardness, so the interface between the first and second porous layers breaks first in the pencil hardness test. Therefore, the peel strength between the first and second porous layers can be evaluated with the hardness calculated by this measurement. The pencil hardness evaluated as described in the Examples is preferably harder than F, more preferably 2H or more, and even more preferably 4H or more, and the upper limit may be 9H.
[0046] (5-2) Permeance The porous ceramic laminate of the present invention can also reduce the pressure loss of a fluid, and can achieve a flow rate of 1.0 m as evaluated in the Examples described later. 3 / h permeance is 1.00×10 -5 m 3 / (m2 sec Pa), and preferably 3.00×10 -5 m 3 / (m 2 ·sec·Pa), and more preferably 1.00×10 -4 m 3 / (m 2 ·sec·Pa) or more, and the upper limit is not particularly limited, but for example, 1.0×10 -3 m 3 / (m 2 sec Pa).
[0047] (5-3) Permeance maintenance rate when fluid flow velocity decreases In addition, according to the examples described later, the flow rate of the fluid flowing through the porous ceramic body is 1.0 m 3 Permeance at 0.5m / h 3 The permeance maintenance rate, obtained by dividing the rate by the permeance at 100 / h, can be 1.2 or less, preferably 1.18 or less, more preferably 1.10 or less, and even more preferably 1.04 or less, and the lower limit may be 1.0.
[0048] (6) Manufacturing method of porous ceramic laminate The porous ceramic laminate of the present invention can be produced by preparing a substrate for the first porous layer having a pore diameter of 0.98 to 200 μm and a cumulative pore volume of 0.13 to 0.25 mL / g, preparing a slurry containing the metal oxide Y so that the Ti / Al ratio is 0.005 or more and less than 0.10, applying the slurry to the surface of the substrate, and heat treating the substrate. LD-max is the D of the second porous layer LD-max When the ratio is 10 times or more, it is preferable to subject the substrate for the first porous layer to a water- and oil-repellent treatment, and to apply a slurry containing the oxide Y to the surface of the substrate for the first porous layer that has been treated to be water- and oil-repellent.
[0049] In a preferred embodiment, a porous substrate that satisfies the above-mentioned cumulative pore volume conditions is used, the substrate is treated to be water- and oil-repellent, and a slurry containing metal oxide Y is applied to the water- and oil-repellent treated surface, thereby preventing the slurry from entering the pores of the substrate, and making it easy to adjust the cumulative pore volume V1 of the porous ceramic laminate to the above-mentioned range.
[0050] Methods of water and oil repellency include spray coating, dip coating, bar coating, suction coating, ultrasonic spraying, brush coating, squeegee coating, spray coating, etc. The composition of the water and oil repellent is not limited, but for example, paraffin-based water and oil repellent, fluorine-based water and oil repellent, polysiloxane-based water and oil repellent can be used. Fluorine-based water and oil repellent includes those having a perfluoroalkyl group and those having a perfluoropolyether structure.
[0051] Furthermore, by controlling the Ti / Al ratio of the metal oxide Y-containing slurry to be 0.005 or more and less than 0.10, the Ti / Al ratio in the second porous layer of the porous ceramic laminate of the present invention can be controlled.
[0052] The metal oxide Y contained in the slurry may be one type or two or more types, and it is sufficient that Ti and Al are contained in the metal oxide Y. The metal oxide contained in the slurry preferably contains any one of TiO2, Al2O3, and a composite oxide containing Ti and Al.
[0053] The average particle size of the metal oxide Y contained in the slurry is preferably, for example, 0.01 to 2 μm. In particular, the average particle size of a metal oxide containing Al (e.g., Al2O3, or a composite oxide containing Ti and Al, etc.) is preferably 0.1 to 2 μm, and the average particle size of a metal oxide containing Ti (e.g., TiO2, etc.) is preferably 0.01 to 0.1 μm. The particle size distribution of the metal oxide can be measured using a small-angle X-ray scattering method when the average particle size is about 0.1 μm or less, and can be measured using a laser diffraction / scattering type particle size distribution measuring device when the average particle size is about 0.1 μm or more. The average particle size may be a diameter equivalent to 50% cumulative on a volume basis.
[0054] The concentration of the metal oxide Y in the slurry is, for example, 2 mass % or more and 22 mass % or less, and preferably 4 mass % or more and 17 mass % or less.
[0055] The slurry preferably contains, in addition to the metal oxide Y, a solvent, a thickener, and a dispersant. The solvent may be water or an organic solvent. Examples of the thickener include methyl cellulose, hydroxyethyl methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyalkylene oxide, polyvinyl alcohol, sodium polyacrylate, polyvinylpyrrolidone, polyacrylamide, polydimethylaminoethyl methacrylate, etc. The concentration of the thickener in the slurry is, for example, 0.5% by mass or more and 5% by mass or less, and preferably 1% by mass or more and 4% by mass or less. The dispersant can suppress the aggregation of metal oxide particles in the slurry. The dispersant may be any of cationic surfactants, anionic surfactants, nonionic surfactants, and amphoteric surfactants. Among them, anionic surfactants such as polycarboxylate ammonium salts and polycarboxylate amine salts are preferred, and SN Dispersant 5020, SN Dispersant 5023, SN Dispersant 5027, SN Dispersant 5468, Noparfa D-6010, Nopcol 5200, Nopcosant RFA, Nopcosperse 6100, and Nopcosperse 6150 manufactured by San Nopco Co., Ltd. may be used. The concentration of the dispersant in the slurry is, for example, 0.1% by mass or more and 3% by mass or less, and preferably 0.3% by mass or more and 1% by mass or less.
[0056] After the slurry is applied, a heat treatment may be performed. The heat treatment temperature is, for example, 1000° C. or more and 1500° C. or less, and the heat treatment time is, for example, 1 hour or more and 8 hours or less.
[0057] (7) Separation membrane The porous ceramic laminate of the present invention can be used as a microfiltration membrane, an ultrafiltration membrane, or a nanofiltration membrane, and can be further laminated with a functional membrane as necessary to be used as a microfiltration membrane, an ultrafiltration membrane, a nanofiltration membrane, a reverse osmosis membrane, an ion exchange membrane, a separation membrane for gases, etc.
[0058] Examples of the functional membrane described above include zeolite, MOF (Metal Organic Frameworks), porous silica membrane, and porous alumina membrane. A separation membrane with a functional layer can be produced by applying a liquid containing inorganic particles or MOF that constitute a functional layer to the surface of the ceramic porous laminate obtained by the present invention and reacting it. The synthesis conditions can be appropriately selected depending on the functional layer to be laminated, and may be, for example, 80 to 800°C for 1 to 72 hours. EXAMPLES
[0059] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples, and can of course be modified within the scope of the above and below-mentioned aims, and all such modifications are within the technical scope of the present invention.
[0060] The materials used in the following Examples and Comparative Examples and the resulting porous ceramic laminates were evaluated by the following methods.
[0061] (1) Measurement of metal content in the substrate (first porous layer) The Fe, Al, Na, and Si contents of the substrate (first porous layer) were measured using an X-ray fluorescence analyzer (XRF, manufactured by Rigaku Corporation, ZSX PrimusII) by the FP method.
[0062] (2) Method for measuring particle size of metal oxides The particle size distribution of the alumina used in the examples and comparative examples was measured using a laser diffraction / scattering particle size distribution measuring device (Microtrac MT3300EX II, 0.2 mass% aqueous solution of sodium hexametaphosphate, manufactured by Microtrac Corporation), and the volume-based cumulative 50% equivalent diameter was measured.
[0063] (3) Cumulative pore volume V1 of pores with diameters of 0.98 to 200 μm and cumulative pore volume Vt of pores with diameters of 0.112 to 200 μm The substrate itself and the laminates prepared in the examples and comparative examples were each dried at 120°C for 4 hours, and then measured by mercury intrusion using an Autopore IV9520 (manufactured by Micromeritics) to measure the cumulative pore volume of the substrate and the cumulative pore volumes V1 and Vt of the laminates. The details of the measurement conditions are as follows. Hg Surface Tension:480.000dynes / cm Hg Density: 13.5335g / mL Adv. Contact Angle:140.000degrees Rec. Contact Angle:140.000degrees Pen. Constant: 11.007μL / pF Pen. Weight: 1.0000g Stem Volume: 0.3920mL Max. Head Pressure: 4.4500psia Pen. Volume: 1.0000mL Assembly Weight: 141.0000g Low Pressure(Evacuation Pressure):50μmHg Evacuation Time: 10 seconds Mercury Filling Pressure:1.03psia Equilibration Time: 10 seconds High Pressure(Evacuation Time):10secs Maximum Intrusion Volume:0mL / g
[0064] (4) Pencil hardness measurement The porous ceramic laminates obtained in the examples and comparative examples were evaluated according to JIS K5600 General Test Method for Paint Scratch Hardness (Pencil Method) 5-4. A pencil hardness tester (Yasuda Seiki Seisakusho Co., Ltd. 533-M1, weight: 750g, pencil moving speed: 1mm / sec) was used to draw a line with a soft pencil (Mitsubishi Pencil Co., Ltd.: Mitsubishi Uniseries 6B-9H) on the surface of the laminate (the surface opposite to the first porous ceramic layer), and the surface was observed using a digital microscope (Keyence Corporation: VHX-5000), and the hardness just before the hardness at which peeling, dents, or scratches were observed was evaluated as the hardness of the sample.
[0065] (5) Permeance measurement Air was blown from the outside of the cylindrical porous ceramic laminate sample at a distance of 1.0 m. 3The air was allowed to flow at a constant flow rate of 100 / h, and the air that permeated from the inside of the sample was allowed to flow downstream. At this time, the pressure difference between the upstream and downstream sides was measured. The measurement results were converted using the following formula to obtain the permeance. Note that a higher permeance value means a lower pressure loss.
[0066]
number
[0067] (6) Evaluation of permeance maintenance rate when gas flow velocity decreases Air is blown 0.5 m from the outside of the cylindrical sample. 3 / h, and 1.0m 3 The air was passed through the sample at a constant flow rate of 1.0 m / h, and the air that had permeated through the sample was passed downstream. At this time, the pressure difference between the upstream and downstream sides was measured. From the measurement results, the permeance of each side was calculated using an equation similar to that of equation (1) above. 3 / h permeance at low flow rate of 0.5m 3 The permeance maintenance rate when the gas flow rate is reduced was calculated by dividing the permeance at the time of gas flow rate reduction by the permeance at the time of gas flow rate reduction at the time of gas flow rate reduction. The lower the permeance maintenance rate, the more it is possible to suppress the reduction in permeance when the gas flow rate is reduced.
[0068] Example 1 As the substrate (first porous layer), a commercially available ceramic substrate E1 (cylindrical shape with an inner diameter of 7.0 mm, an outer diameter of 10.0 mm, a length of 10 cm, a Na / Ca mass ratio of 1.76, and a Na / Al mass ratio of 0.00212) containing Al2O3 and having a pore diameter of 0.98 to 200 μm and a cumulative pore volume of 0.145 mL / g was prepared. The substrate was dipped in a water repellent SH Conc (containing fluororesin and petroleum-based hydrocarbons) manufactured by Columbus Co., Ltd., and dried at room temperature for 12 hours or more. Next, alumina powder AKP-3000 manufactured by Sumitomo Chemical Co., Ltd. and a titanium oxide slurry (STS-21: manufactured by Ishihara Sangyo Kaisha, Ltd., 40 wt%) were mixed so that the molar ratio of Ti / Al was 0.0336. The volume-based cumulative 50% equivalent diameter of the alumina powder AKP-3000 is about 0.67 μm, and the X-ray particle diameter (catalog value) of the titanium oxide is 20 nm. A mixture of the alumina powder and the titanium oxide slurry was mixed with hydroxypropyl methylcellulose 65SH-30000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, SN Dispersant 5468 as a dispersant, and water to prepare a slurry. The concentrations of alumina, thickener, and dispersant in the slurry were 5 wt%, 1.5 wt%, and 0.5 wt%, respectively. The upper and lower ends of the substrate (after the water-repellent treatment) were sealed so that the slurry would not enter the inner peripheral surface of the substrate, and the substrate was dip-coated with the slurry. Thereafter, the substrate with the slurry applied to the outer peripheral surface was heat-treated at 1200° C. for 3 hours, and a porous ceramic laminate in which a second porous layer (hardened layer of the slurry) was formed on the substrate (first porous layer) was obtained.
[0069] Example 2 A porous ceramic laminate of Example 2 was obtained in the same manner as in Example 1, except that a commercially available ceramic substrate E2 (cylindrical shape with an inner diameter of 7.2 mm, an outer diameter of 9.5 mm, and a length of 10 cm, with a cumulative pore volume of 0.209 mL / g with pore diameters of 0.98 to 200 μm and a Na / Ca mass ratio of 5.65 and a Na / Al mass ratio of 0.0178) containing Al2O3 was used as the substrate (first porous layer).
[0070] Example 3 A porous ceramic laminate of Example 3 was obtained in the same manner as in Example 1, except that a commercially available ceramic substrate E3 (cylindrical shape with an inner diameter of 6.9 mm, an outer diameter of 10.0 mm, and a length of 10 cm, with a cumulative pore volume of 0.24 mL / g with pore diameters of 0.98 to 200 μm and a length of 10 cm, a Na / Ca mass ratio of 52.7, and a Na / Al mass ratio of 0.0322) containing Al2O3 was used as the substrate (first porous layer).
[0071] Example 4 A porous ceramic laminate of Example 4 was obtained in the same manner as in Example 1, except that the Al in the alumina powder and the Ti in the titanium oxide slurry were mixed so that the molar ratio of Ti / Al was 0.0130.
[0072] Example 5 A porous ceramic laminate of Example 5 was obtained in the same manner as in Example 1, except that the Al in the alumina powder and the Ti in the titanium oxide slurry were mixed so that the molar ratio of Ti / Al was 0.0555.
[0073] Example 6 A porous ceramic laminate of Example 6 was obtained in the same manner as in Example 2, except that the Al in the alumina powder and the Ti in the titanium oxide slurry were mixed so that the molar ratio of Ti / Al was 0.00645.
[0074] Example 7 A porous ceramic laminate of Example 7 was obtained in the same manner as in Example 2, except that the Al in the alumina powder and the Ti in the titanium oxide slurry were mixed so that the molar ratio of Ti / Al was 0.0197.
[0075] Example 8 A porous ceramic laminate of Example 8 was obtained in the same manner as in Example 2, except that the Al in the alumina powder and the Ti in the titanium oxide slurry were mixed so that the molar ratio of Ti / Al was 0.0709.
[0076] Comparative Example 1 A porous ceramic laminate of Comparative Example 1 was obtained in the same manner as in Example 1, except that a commercially available ceramic substrate C1 (cylindrical shape with an inner diameter of 6.0 mm, an outer diameter of 9.9 mm, and a length of 10 cm, with a cumulative pore volume of 0.113 mL / g with pore diameters of 0.98 to 200 μm and a Na / Ca mass ratio of 0, and a Na / Al mass ratio of 0) containing Al2O3 was used as the substrate (first porous layer).
[0077] Comparative Example 2 A porous ceramic laminate of Comparative Example 2 was obtained in the same manner as in Example 1, except that a commercially available ceramic substrate C2 (cylindrical shape with an inner diameter of 3.3 mm, an outer diameter of 6.0 mm, and a length of 10 cm, with a cumulative pore volume of 0.259 mL / g with pore diameters of 0.98 to 200 μm and a Na / Ca mass ratio of 0.338 and a Na / Al mass ratio of 0.00488) containing Al2O3 was used as the substrate (first porous layer).
[0078] The results are shown in Table 1.
[0079] [Table 1]
[0080] Furthermore, the following measurements were carried out for the examples and comparative examples. (7) Measurement of pore distribution of the first and second porous layers In the measurement by mercury intrusion porosimetry described in the above item (3), in addition to measuring the entire porous ceramic laminate, only the substrate corresponding to the first porous layer was also measured. In the log differential pore volume distribution with the pore diameter on the horizontal axis, one peak was observed in the measurement of only the substrate, and two peaks were observed in the measurement of the entire porous ceramic laminate. The peak (maximum value of the log differential pore volume) observed in the measurement of only the substrate gave the pore diameter D LD-max The D of the second porous layer was evaluated, and the peak on the lower pore diameter side of the two peaks observed in the observation of the entire porous ceramic laminate was determined to be the D of the second porous layer. LD-max was evaluated.
[0081] (8) Thickness of the second porous layer The cylindrical porous ceramic laminate was embedded in resin and polished to obtain a cross section perpendicular to the axial direction (i.e., a cross section parallel to the stacking direction of the first porous layer and the second porous layer), which was then observed with a scanning electron microscope (SEM). An image was obtained so that the total length of the surface of the second porous layer on the first porous layer side was 1.5 mm or more in the circumferential direction, and only the second porous layer was extracted by image analysis. The thickness (length in the stacking direction) of the second porous layer in the obtained image was then measured at five or more points, and the average value of the thicknesses measured at the multiple points was taken as the thickness of the second porous layer.
[0082] As a result of the measurement according to (7) above, the pore diameter D of the first porous layer LD-max In Examples 1, 4, and 5, the pore diameter was 1.5 μm, in Examples 2, 6, 7, and 8, the pore diameter was 15 μm, in Example 3, the pore diameter was 8.5 μm, in Comparative Example 1, the pore diameter was 8.5 μm, and in Comparative Example 2, the pore diameter was 0.98 μm. LD-max The results were as follows: Example 1 was 0.41 μm, Example 2 was 0.27 μm, Example 3 was 0.27 μm, Example 4 was 0.46 μm, Example 5 was 0.37 μm, Example 6 was 0.28 μm, Example 7 was 0.27 μm, Example 8 was 0.30 μm, Comparative Example 1 was 0.28 μm, and Comparative Example 2 was 0.11 μm.
[0083] The thickness of the second porous layer was measured according to (8) above, and as a result, it was 34.8 μm in Example 2, 35.9 μm in Example 3, and 53.1 μm in Comparative Example 1.
Claims
1. A porous ceramic laminate having a first porous layer and a second porous layer directly laminated on the first porous layer, the first porous layer contains a metal oxide X; the second porous layer includes a metal oxide Y, the metal oxide Y including Ti and Al; the molar ratio of Ti / Al in the second porous layer is 0.005 or more and less than 0.10; A porous ceramic laminate having a cumulative pore volume V1 of pores with diameters of 0.98 to 200 μm of 0.115 mL / g or more and less than 0.259 mL / g.
2. The porous ceramic laminate according to claim 1 , wherein the first porous layer contains Na and Ca elements, and a mass ratio of Na / Ca in the first porous layer is greater than 1.16 and less than 100.
3. 3. The porous ceramic laminate according to claim 1, wherein the first porous layer contains Na and Al, and the mass ratio of Na / Al in the first porous layer is greater than 0.0049 and less than 0.
10.
4. 3. The porous ceramic laminate according to claim 1, wherein the cumulative pore volume V1:V1 / Vt of pores having a pore diameter of 0.98 to 200 μm relative to the cumulative pore volume Vt of pores having a pore diameter of 0.112 to 200 μm is more than 0.88 and less than 0.
99.
5. The metal oxide X is Al 2 O 3 The porous ceramic laminate according to claim 1 or 2, comprising:
6. 3. The porous ceramic laminate according to claim 1, which is in the form of a tube or a monolith.
7. A separation membrane comprising the porous ceramic laminate according to claim 1 or 2.
Citation Information
Patent Citations
Porous ceramic body and method of manufacturing glass used for binder thereof
JP2003238257A
Monolithic separation membrane structure and method for producing same
WO2015146571A1